IDENTIFYING STRATEGIES OF GRADE VIII STUDENTS IN LEARNING VOCABULARY AT SMP NEGERI 1 WITAPONDA MOROWALI - Dwi Lestari, Putri; Mukrim, Mukrim; Hasyim, Zarkiani; Rofiqoh, Rofiqoh (Tadulako University, 2024)
The objective of this research was to find out vocabulary learning strategies applied by the students and also the most frequently applied strategies. In this research, the researchers ought to find vocabulary learning strategies-based Schmitt’s taxonomy due to the fact that it is a comprehensive inventory of vocabulary learning strategies that covers all of strategies commonly applied by English learners. This research applied quantitative research method with survey approach. Population of this study was the whole of the seven grade students at SMP Negeri 1 Witaponda in academic year of 2021/2022. The subjects of this research were grade eight students in SMP Negeri 1 WitaPonda By quota sampling, the participants in this study were 5 representative students of each class which would be 30 in total. The instrument used in this research was questionnaire, based on Schmitt's (1997) taxonomy. Based on the findings, the researcher concludes that there are several strategies used by the students. They are 1) using electronic dictionary to know the meaning of the word, 2) using Indonesian-English dictionary, 3) connecting one word to word related with it, 4) seeing description in text to explain meaning of a word, 5) labeling English word on object for helping them to remember vocabulary. The second conclusion is the most dominant strategies used by the students is determination strategies.